Radial force control for triple three-phase sectored SPM machines. Part I: Machine model - Sala, Giacomo; Gerada, David; Gerada, C.; Tani, A. (2017)
The radial force control technique for a triple three-phase Surface Permanent Magnet (SPM) machine is investigated in this paper. The machine has a nine-phase winding arranged in three sectors and supplied by three different Voltage Source Inverters (VSI). A machine model is developed, based on the multi space vector approach. The multi space vector current control technique is exploited to control the torque and the radial force. The radial force control can be useful to compensate for a bearing fault or for a rotor eccentricity. Finite element simulations are used to validate the model and the control technique. Finally, criticalities of the control and modelling aspects are discussed.